Enhancing vibration attenuation in offshore wind turbine with multiphysics mechanical metamaterial - Machado, Marcela Rodrigues (2026)
Wind energy harvesting is performed by wind turbines that convert wind into energy, contributing significantly to the increase in renewable energy globally. However, they encounter significant issues with structural vibrations caused by the operational environment, such as wind, wave, and seismic activities, which lead to malfunction, fatigue, and decreased efficiency. This paper proposes innovative metamaterial wind turbine designs that enhance vibration attenuation in offshore wind turbines by incorporating tuned liquid and multiphysics resonators. The locally resonant control mechanism improves the damping in the system by reducing displacement amplitude. These control strategies are tested under hazards, including wind, wave, and blade rotation, and evaluate various liquid configurations to determine optimal performance. The findings show a substantial reduction in overall vibration amplitude, achieving up to 60% of vibration amplitude attenuation, compared to 7.8% with traditional tuned mass dampers. Aside from outstanding performance in vibration control, these metamaterial turbines incorporate compacted dynamic resonators in their configuration compared to traditional passive controllers. Hence, the proposed design associates small controllers and brings together the concept of multiphysics metamaterials. The paper elaborates on the design and modelling of the turbine metamaterial and the resonators using the dynamic stiffness method. This research underscores the potential of metamaterials to advance wind turbine technology through enhanced vibration control, representing a significant advancement in the design and reliability of wind energy systems.